KEMAMPUAN ARTIFICIAL SEAGRASS TERHADAP KEBERHASILAN TRANSPLANTASI KARANG DI TURUN ABAN SUNGAILIAT - Muhammad Tison; Wahyu Adi; Indra Ambalika (Akuatik: Jurnal Sumberdaya Perairan, 2016)
The condition of the coral reefs of Islands of Bangka Belitung when it has been damaged, one of the solutions to overcome the damage to coral reefs is to transplant coral. Types of coral that are used for research is the goal of this research is Acropora brancing is to know the growth, the rate of mortality and physical parameters of influence of chemical environment against coral transplantation types. Data retrieval is done on the beach Down Aban, Sungailiat in March – June 2015 which lay at a depth of 4 meters. The observed environmental parameters are temperature, salinity, current speed, the rate of sedimentation and brightness. Variable coral observed is high, the relative growth of value added,survival, and mortality index. The results of the measurements of environmental parameters Temperature averages 28, 33oC, the rate of sedimentation (in CTAS 0.185 Mg/Cm/day) and (outside of CTAS 0.1404 Mg/Cm/day), the average Salinity is 32,167 ‰, the average flow Velocity of 0, 167m/s, and brightness 61.75%. Added observations of high coral transplantation in the treatment of 70 CTAS 13.2 mm, 100 of CTAS 3.4 mm, whereas for the control of 13.2 mm. relative Growth on a coral transplantation in the treatment of 70 CTAS 11.07% 100 of CTAS, 2.8%, whereas for the control of 16.2%, survival rates in treatment of CTAS 70 of 83,3%, treatment of CTAS 100 83.3% and while control 75% At the treatment the mortality Index, CTAS 70 of 16.7%, CTAS treatment 100 of 16.7%. While the control by 15%